A Randomized Study of Comparison of Intravenous Dexmedetomidine and Intravenous Esmolol to Attenuate the Cardiovascular Responses to Laryngoscopy and Endotracheal Intubation (Global Journal of Medical Research, 2020)
Design Prospective Randomized controlled study Aims Objective is to compare the efficacy of intravenous Dexmedetomidine and Esmolol in attenuating the cardiovascular pressor responses to laryngoscopy and endotracheal intubation Method Study was done on 60 adults ASA grade I or II normotensive patients undergoing elective surgery under general anaesthesia and willing to participate These patients were be randomly allocated in to either group E Esmolol or D Dexmedetomidine Group D patients were given intravenous Dexmedetomidine infusion 1 mcg kg over 10 minutes 3 minutes before start of laryngoscopy Group E patients were given intravenous Esmolol 1 5 mg kg 2 minutes before start of laryngoscopy All patients were premedicated induced and intubated using Thiopentone and Succinyl Choline as per the protocol
Keywords: laryngoscopy; intubation; Esmolol; hemodynamic; reponse; dexmedetomidine